2010
DOI: 10.1177/0748233710386410
|View full text |Cite
|
Sign up to set email alerts
|

Corrections to: ‘‘Age distribution of cancer in mice’’

Abstract: We found a crucial error in an earlier paper on cancer in elderly mice, Age distribution of cancer in mice: the incidence turnover at old age (Pompei et al., 2001). That paper's principal data set, the ED01 records, was scrambled when read and analyzed with a statistical software package. Having done our best to correct the error, and having subjected the data to a more exact extension of originally published methods, we arrive at conclusions significantly different from those proposed in the original article.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These data do not exclude other potential causes, such as the "weeding out of the susceptible" (8,10,11). It is also notable that cancer incidence rates do not decelerate in mice (20). This fact, combined with our discovery of a major difference between mice and humans with respect to normal cell division rates, provides further evidence for the causal relationship between cancer incidence and the replicative mutations that occur when normal stem cells divide (22,(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These data do not exclude other potential causes, such as the "weeding out of the susceptible" (8,10,11). It is also notable that cancer incidence rates do not decelerate in mice (20). This fact, combined with our discovery of a major difference between mice and humans with respect to normal cell division rates, provides further evidence for the causal relationship between cancer incidence and the replicative mutations that occur when normal stem cells divide (22,(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 85%
“…Cell Division Rates Do Not Decelerate in Laboratory Mice. Although cancer incidence decelerates at advanced age in humans, no deceleration occurs in mice (20). We wondered whether this difference might reflect differences in stem cell division rates in older individuals of the 2 species (21,22).…”
Section: Significancementioning
confidence: 98%
“…Miyaishi et al32 found that, in 331 F344/N rats, all animals that survived for >30 months died of cancer. Unfortunately, it has been discovered that the results reported by Pompei et al,36 who found a mortality peak in BALB/C mice, are entirely incorrect 37…”
Section: Discussionmentioning
confidence: 94%
“…Unfortunately, it has been discovered that the results reported by Pompei et al, 36 who found a mortality peak in BALB/C mice, are entirely incorrect. 37 Although previous work and our results evidence a decline in the age-specific incidence and mortality of most cancers at very old ages, this does not explain why such a decline would occur.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
“…Several factors likely contribute to the diminished incidence in older adults, including that the data may not be as reliable for older individuals (3). This explanation is insufficient, however, as studies in animal models demonstrate the same pattern (4). A second contributing factor is variation among individuals in intrinsic cancer susceptibility, also referred to as frailty (5).…”
Section: Introductionmentioning
confidence: 99%